Criminal Claims in Civil Suits over Insults in the Dutch Republic (17th and 18th Centuries) - Erik Jan Broers (Revista Brasileira de Direito Processual Penal, 2021)
In the Early-Modern Age, concepts like honour and reputation were considered of great importance. When a person suffered a severe insult, he often was more than willing to go to court and sue the offender. The claims the victim filed in most cases, included an ancient penal action rooted in Roman law. The contents of this action consisted in a demand for a pecuniary fine, which the defendant had to pay to a good cause. The plaintiff combined this claim with a second claim, demanding rehabilitation and restoration of his good name by his adversary. However, in many cases the court tried to avoid a legal battle between the opponents and tried to achieve a settlement that would be satisfactory to both of them. If so, the court ordered both parties to appear before two examining judges, who would act as mediators and try to help the adversaries to settle their dispute.